The Role of Social Media Preaching Content on Understanding Islam Among Adolescents in Lentea Village, South Kaledupa District, Wakatobi Regency - Arman, Arman; Rahim, Abdul; Rusli, Rusli (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
This study analyzes the impact of social media content on the understanding of Islam in Lentea Village, South Kaledupa District, Wakatobi Regency. Social media is the main means of spreading Islamic teachings in the digital era. With a qualitative approach and case study method, data were collected through observation, documentation, and interviews with active social media users. The results of the study indicate that da'wah content on social media plays an important role in increasing the understanding of Islam, especially for the younger generation. In addition to forming religious attitudes and behavior, social media also faces challenges, such as the lack of quality content. The main inhibiting factor is the limited facilities and forums for religious activities. Therefore, synergy between the community, religious leaders, and the government is needed to provide adequate facilities. The use of social media as a da'wah medium also needs to be continuously developed so that it has a wider impact in increasing the understanding of Islam and shaping the character of the younger generation.